(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
Aeromycoflora in relation to occurrence and prevalence, their seasonal variation and distribution of fungal spores in air was studied from October, 2010 to September, 2011. During the study a total of 31 fungal species belonging to 18 genera of fungi were isolated and identified. Total fungal colony count was 2308. The highest occurrence and prevalence of fungi was contributed by Aspergillus niger 1075 colonies, Penicillium spp. 582 colonies, Aspergillus fumigatus 167, A. flavus 112 colonies, Rhizopus sp. 121 colonies, Candida spp. 39 colonies, Chladosporium spp. 36 colonies, Syncephalestrum sp. 25 colonies, and Fusarium spp. 14 colonies. Lowest colony countwas recorded one, in Aspergillus ustus, Drechslera sp., Nigrospora sp. and Ulocladium sp. Maximum fungal pollutants were found 339 in July, 2010 at temperature 27.12°C and moisture 84.2% during the wet and rainy days and declined in January, 2011 when temperature and moisture label decreased to 20.26°C and 59.5%, respectively. Highest colony density was recorded in July, 2011, it was moderate in February and March, 2011. Lowest colony density was recorded in January and May, 2011 DOI: http://dx.doi.org/10.3329/jbas.v38i1.20211 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 1, 49-59, 2014